Modeling and Validating the Clinical Information Systems Policy Using Alloy - Haraty, Ramzi A. (2013)
Information systems security defines three properties of information: confidentiality, integrity, and availability. These characteristics remain major concerns throughout the commercial and military industry. In this work, we focus on the integrity aspect of commercial security applications by exploring the nature and scope of the famous integrity policy - the Clinical Information Systems Policy. We model it and check its consistency using the Alloy Analyzer.